Viscosity of set-style yogurt as influenced by heat treatment of milk and added demineralized whey powder - Đurđević-Denin Jelena D. (Journal of Agricultural Sciences (Belgrade), 2002)
Skim milk powder was reconstituted to obtain milk A (with 8.44% TS). Milk sample A was standardized with different amounts of demineralized whey powder (DWP) to obtain milk B (with 9.71% TS) and milk C (with 10.75% TS). Milk samples were heat treated at 85ºC/20 min and 90ºC/10 min, respectively. Untreated milk was used as control. Milk samples were inoculated with 2.5% of commercial yogurt culture (containing Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus in the ratio 1:1) at 43ºC. Samples were incubated until pH 4.6 was reached. Samples were immediately cooled to 4ºC and held at that temperature until analyses. Measurements of viscosity were done with Brookfield DV-E Viscometer. Spindle No 3 at 20 rpm was used for all samples. After 1 day of storage, set-style yogurt samples produced from untreated milk had the highest, while samples produced from milk heat treated at 90ºC/10 min the smallest initial viscosity, regadless of the dry matter content and composition. Average viscosity of set-style yogurts decreased with intensifying temperature of applied heat-treatment. During storage, set-style yogurt samples produced from milk heat treated at 90ºC/10 min had the least pronounced decrease of viscosity during shearing. After 14 days of storage, set-style yogurt samples produced from milk standardized with demineralized whey powder had higher viscosity than samples produced from basis milk.